Comorbidities and Risk Factors for Severe Outcomes in COVID-19 Patients in Saudi Arabia: A Retrospective Cohort Study - Shaikh,Fatema S; Aldhafferi,Nahier; Buker,Areej; Alqahtani,Abdullah; Dey,Subhodeep; Abdulhamid,Saema; AlBuhairi,Dalal Ali Mahaii; Alkabour,Raha Saud Abdulaziz; Atiyah,Waad Sami O; Bachar Chrouf,Sara; Alshehri,Abdussalam; Olatunji,Sunday Olusanya; et al. (Journal of Multidisciplinary Healthcare, 2021)
Fatema S Shaikh,1 Nahier Aldhafferi,1 Areej Buker,1 Abdullah Alqahtani,1 Subhodeep Dey,2 Saema Abdulhamid,1 Dalal Ali Mahaii AlBuhairi,1 Raha Saud Abdulaziz Alkabour,1 Waad Sami O Atiyah,1 Sara Bachar Chrouf,1 Abdussalam Alshehri,3 Sunday Olusanya Olatunji,1 Abdullah M Almuhaideb,1 Mohammed S Alshahrani,4 Yousof AlMunsour,1 Vahitha B Abdul-Salam5 1College of Computer Science and Information Technology, Imam Abdulrahman Bin Faisal University, Dammam, Eastern Province, Saudi Arabia; 2Indian Institute of Management – Calcutta, Kolkata, India; 3Prince Mohammed bin Abdulaziz Hospital, Riyadh, Saudi Arabia; 4College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Eastern Province, Saudi Arabia; 5Centre for Cardiovascular Medicine and Device Innovation, William Harvey Research Institute, Barts and The London School of Medicine and Dentistry, Queen Mary University of London, London, UKCorrespondence: Fatema S Shaikh Tel +966-5591660024Email fsshaikh@iau.edu.saPurpose: The first novel coronavirus disease-19 (COVID-19) case in the Kingdom of Saudi Arabia (KSA) was reported in Qatif in March 2020 with continual increase in infection and mortality rates since then. In this study, we aim to determine risk factors which effect severity and mortality rates in a cohort of hospitalized COVID-19 patients in KSA.Method: We reviewed medical records of hospitalized patients with confirmed COVID-19 positive results via reverse-transcriptase-polymerase-chain-reaction (RT-PCR) tests at Prince Mohammed Bin Abdulaziz Hospital, Riyadh between May and August 2020. Data were obtained for patient’s demography, body mass index (BMI), and comorbidities. Additional data on patients that required intensive care unit (ICU) admission and clinical outcomes were recorded and analyzed with Python Pandas.Results: A total of 565 COVID-19 positive patients were inducted in the study out of which, 63 (11.1%) patients died while 101 (17.9%) patients required ICU admission. Disease incidences were significantly higher in males and ...